(untitled) (Lafia Journal of Scientific and Industrial Research, 2024)
A total of Forty-five vertical electrical soundings (VES) were conducted using Schlumberger electrode configuration to map the groundwater condition in the Awe Brine Field, Nasarawa, Nigeria. The result of the study exhibited significant variations in resistivity across the area, which allowed the generation of iso-resistivity contour maps for four distinct geoelectric layers. The first layer, consisting of a thin top layer of unconsolidated material, displayed resistivity values ranging from 85 Ωm to 2437.8 Ωm. The second layer, composed of shale-sandstone, has a resistivity between 1.2 Ωm to 785 Ωm. The third layer showed resistivity ranging from 1.2 Ωm to 430.5 Ωm. it was observed that a thick layer of sandy clay contained fresh water, with resistivity levels ranging from 27 Ωm to 1825.9 Ωm. The Dar Zarrouk parameters were calculated to evaluate the protective attributes of the aquifers. The analysis revealed that the longitudinal conductance (Sc) ranged from 0.06 to 3.86 S, the longitudinal resistivity (ρL)) ranged from 71.66 to 3830.4 Ωm, and the transverse resistance (TR) ranged between 2.55 and 1102.18 Ω. Based on the resistivity values and thickness of the geoelectric layers, the researchers identified four distinct aquifer zones labelled A, B, C, and D. Notably, the third layer, referred to as the C horizon, displayed significantly lower resistivity and higher salinity compared to the other layers. This layer corresponds to the Awe Formation, renowned for its brine deposits. Consequently, the study suggests that exploring freshwater resources near New Awe is more promising than the Old Awe area